IMPROVING STUDENTS' SPEAKING SKILL BY USING ROLE PLAY (AN ACTION RESEARCH AT THE TENTH YEAR OF SMA N 1 GEMOLONGIN 2010/2011 ACADEMIC YEAR) - YUANITA, DYAH NINDYA (2011)
This research paper aims at describing the implementation of teaching speaking using role play at the tenth year of SMA N 1 Gemolong in 2010/2011 academic year, and the students' speaking skill improvement. The writer conducts classroom action research (CAR). The data are taken from event, informant, and document. The methods of collecting data are observation, document, test, and interview with the teacher and the students. The results of the study show that first, the role play is effective to improve on speaking skill. It is proved that the students talk actively, the students get self-confidence, the student speaks fluently, the student can speak spontaneously without opening the text, and the students get better grammar, pronunciation, and vocabulary. Second, the role play makes the students' speaking skill improve in descriptive text at the tenth year of SMA N 1 Gemolong in 2010/2011 academic year. The students' speaking improvement can be seen from the average score. The researcher takes assignment note, that are Pre-test, they get 62 average score, in cycle I, they get 73 average score, while in cycle II, they get 90 average score. The Post-test, they get 90 average score, it has similiar score in cycle II because the researcher takes the students' result asssignment become the posttest. They get 28 score improvement. It is so great result in the last meeting. So the role play can improve the students' speaking skill step by step. ing,